Câncer do colo do útero em idosas: análise dos fatores associados e da distribuição espacial - VERZARO, Pabline Medeiros (2018)
Objective: to associate sociodemographic and clinical variables with staging of cervical cancer in the elderly of an oncology reference hospital. Methodology: This is an observational, retrospective and analytical study. A total of 559 elderly women were studied for the statistical calculation, using the statistical program SPSS v. 19, considering a level of significance of 0.05. Results: The variables that presented a statistically significant correlation with the staging of cervical cancer were: married women (p = 0.018), histopathologic type squamous cell carcinoma (p = 0.002), radiotherapy + chemotherapy as the first treatment received in the hospital (p = 0.021), complete remission of the disease at the end of the first treatment (p = 0.000), without cancer deaths (p = 0.000) and never smoked (p = 0.03). Conclusion: The data from the study reaffirms the need for prevention and active search of cases. Knowing the epidemiological characteristics of these elderly women, attended at a hospital of oncological reference, becomes significant, since it provides subsidy for the planning evaluation of effective programs in the control of cervical cancer.